Soekarno's Rhetoric in Anti-Imperialism and Anti-Capitalism International Communication (Oratio Directa, 2018)
This study examines Soekarno’s rhetoric in international communication, particularly his consistent opposition to imperialism and capitalism. Invitational rhetoric explains how Soekarno opened space for audiences to understand an alternative perspective on colonial domination and international solidarity. His speeches and political actions helped build awareness and solidarity among colonized countries, including cooperation between Asian and African nations. The analysis also considers ethos, pathos, and logos as persuasive elements in Soekarno’s international rhetoric.
Keywords: Soekarno’s Rhetoric; International Communication; Imperialism; Capitalism; Diplomacy